1972
DOI: 10.1071/bi9720861
|View full text |Cite
|
Sign up to set email alerts
|

Oospore Production in Phytophthora Cinnamomi in the Presence of Trichoderma Koningii

Abstract: The soil-borne fungus Phytophthora cinnamomi Rands is a particularly impor-tant pathogen in Australia because of its consistent association with root-rot disease of a wide variety of exotic and native plant species. It was thought originally to have been introduced from south-east Asia (Crandall and Gravatt 1967), but evidence recently obtained (Pratt, Heather, and Shepherd, unpublished data), suggests that it may be indigenous to eastern Australia and may have been partly instrumental in determining the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
1
Order By: Relevance
“…In addition, strains of T. koningii afforded a serie of cyclopentenes named homothallin I (121) (Pratt et al 1972;Edenborough and Herbert 1988), homothallin II (122), and the amine-, formamide-, and N,N-dimethylamine-derivatives from 122 (123-125) (Edenborough and Herbert 1988;Mukhopadhyay et al 1996). Production of homothallin II (122) by a UV-induced mutant strain of T. harzianum has been also reported .…”
Section: Isocyano Metabolitesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, strains of T. koningii afforded a serie of cyclopentenes named homothallin I (121) (Pratt et al 1972;Edenborough and Herbert 1988), homothallin II (122), and the amine-, formamide-, and N,N-dimethylamine-derivatives from 122 (123-125) (Edenborough and Herbert 1988;Mukhopadhyay et al 1996). Production of homothallin II (122) by a UV-induced mutant strain of T. harzianum has been also reported .…”
Section: Isocyano Metabolitesmentioning
confidence: 92%
“…and other effects on fungal morphology (Pratt et al 1972;Reeves and Jackson 1972;Brasier 1975); (III) inhibition of the enzyme tyrosinase and its implication for melanin biosynthesis in mammals (Lee et al 1997a, b). …”
Section: Isocyano Metabolitesmentioning
confidence: 99%
“…P. cinnamomi is ostensibly heterothallic although sexual reproduction through selfing does occur in the A2 mating type in the presence of external agents such as Trichoderma spp. (Brasier, , ,b; Pratt, Sedgley, Heather, & Shepherd, ) and in Acacia roots (Jayasekera, McComb, Shearer, Hardy, & St, ). Crone, McComb, O'Brien, and Hardy () showed that the A2 mating type formed abundant selfed oospores in naturally infected roots of several herbaceous plants showing no symptoms of disease and postulated that the formation of selfed oospores in plant roots was probably common and widespread on asymptomatic hosts.…”
Section: What Does Genetic Variation In A1 Phytophthora Cinnamomi Telmentioning
confidence: 99%
“…The volatile substance produced by Trichoderma koningii which induces oospore development in A2 strains (Brasier, 1971(Brasier, , 1975Pratt et al, 1972), and which thus mimics the effect of a2 hormone, is not a steroid (Sakata & Rickards, 1980), so it would not be surprising if the a1 and a2 hormones themselves were not steroidal.…”
Section: Transfer Of Materials Between Paired Cultures One Of Whichmentioning
confidence: 99%